HYGIENIC SUBSTANTIATION OF A NEW PESTICIDES IN UKRAINE OXATHIAPIPROLIN AND FLUFENACET MAXIMUM ALLOWABLE CONCENTRATION IN THE WATER BODIES USED FOR HOUSEHOLD AND DOMESTIC WATER SUPPLY - Novokhatska , O.O.; Vavrinevych , O.P.; Zinchenko , T.I.; Syrota , A.I. (The Ukrainian Scientific Medical Youth Journal, 2017)
To prevent and decrease negative impact of pesticides on population health, safe levels of its residues in the water should be substantiated. Taking into consideration the fact of absence of regulations in the water of ponds in Ukraine for such substances as oxathiapiprolin and flufenacet, the purpose of the work was hygienic substantiation of this new pesticides in Ukraine maximum allowable concentrations in the water of water bodies used for household and domestic water supply. Taking into account the abovementioned, we have performed experimental studies to substantiate the hygienic standard of studied pesticides in the water using physical- chemical, organoleptic, photometric, chromatographic, and statistical analysis methods. As a result of experimental studies threshold concentrations of oxathiapiprolin and flufenacet were established by the influence: on organoleptic properties of water at the level of 0.02 mg/dm3 and 0.2 mg/dm3, on the general sanitary regimen of pond – 0.0002 mg/dm3 and 0.002 mg/dm3, and on sanitary-toxicological index of hazard – 0.2 mg/dm3 and 0.02 mg/dm3, correspondingly. The findings allowed us to establish a limiting index of hazard (general sanitary) and to substantiate scientific evidence-based MAC of oxathiapiprolin in the water at the level of 0.0002 mg/dm3 and flufenacet – 0.002 mg/dm3.